Sediment dynamics and heavy metal pollution history of the Cruhlig Lake (Danube Delta, Romania). (March 2016) - Begy, Róbert-Csaba; Preoteasa, Luminita; Timar-Gabor, Alida; Mihăiescu, Radu; Tănăselia, Claudiu; Kelemen, Szabolcs; Simon, Hedvig
Abstract: This is the first study reporting recent sedimentation rates data (e.g. the past 120–150 years) for the Cruhlig Lake situated in the Danube Delta. The aim of this study is to analyse the recent sedimentation rates using the 210 Pb dating method and identifying the heavy metal pollutants and their variability in time. Five sediment cores were taken with a gravity corer and – after drying the sliced samples–physical parameters, organic material and inorganic carbon content were determined. The total 210 Pb content was measured via 210 Po by alpha spectrometry, while supported 210 Pb was measured by 226 Ra (trough short life 222 Rn daughters) with HPGe detectors. Heavy metals were determined by ICP-MS; from the 64 measured elements, only exceeding values of Al, As, Cd, Co, Cs, Cr, Cu, Fe, Hg, K, Li, Mg, Mn, Ni, Pb and Zn are discussed. After applying the CRS model, ages and sedimentation rates were calculated. The average sedimentation rate of the Cruhlig Lake is 0.21 ± 0.02 g/cm 2 y, Minimum values (0.05 ± 0.003 g/cm 2 y) are registered along the eastern shoreline of the lake before 1913, while maximum values are recorded due to the flooding in 2006 in the western side (1.34 ± 0.12 g/cm 2 y). Recent sedimentation rates divide the lake into three areas: the secluded eastern near shore part (0.63 ± 0.07 g/cm 2 y), the centre of the lake (0.92 ± 0.05 g/cm 2 y) and the dynamic western area, where most sediment transport takes place (1.13 ± 0.01 g/cm 2 y). The sedimentation pattern proves this lake to be very sensitive to fluvial discharge fluctuations. The building of the Iron Gate dams (1972 and 1985) had a negative impact on the sedimentation decreasing it with 58.74%, while after 1989 these values grew 2.25 times. The lake received a quantity of sediment rich in heavy metals in 1992 ± 3 y, which settled mostly on the eastern part. Values for Cd, Co, Cr, Hg, Pb and Zn are up to five times higher in 1980 ± 5 y in the eastern part of the lake, while Cd, Co, Cr and Ni are twice as high as the values measured for the marine substrate. Values of As show increasing of up to 150% in 2006 ± 2 y throughout the whole surface of the lake. Graphical abstract: Highlights: 210 Pbtotal (210Po) by alpha and 210 Pbsupported  ( 226 Ra) by gamma spectrometry were measured from Danube Delta sediments. 64 elements are measured via ICP-MS, from which 16 of high levels are discussed. The sediment dynamics in last 100 years time scale was investigated. The influence on the sedimentation processes of the construction of the Iron Gates power plant was investigated. Heavy metal contents are discussed in correlation with sediment intake and anthropic events (construction of Iron Gates).